The impact of social media on grade 10 learners' creative essays in Tshivenda home language at Vhumbedzi Circuit, Vhembe District, Limpopo Province, South Africa - Mbuvha, Tshilisanani (My University, 2025)
This study explored the impact of Social Media on Grade 10 Learners’ Creative Essays in Tshivenḓa Home Language at Vhumbedzi Circuit, Vhembe East District, Limpopo Province, South Africa. This follows the researcher’s observations that most Grade 10 Tshivenḓa Home Language learners’ essay writing tasks in Vhumbedzi Circuit are riddled with informal Tshivenḓa register and a range of other language errors associated with the use of Social Media language. These include the use of incorrect capitalization, numerous spelling errors, fragmented sentences, and gross grammatical errors. To get a better understanding of the problem studied, a qualitative case study research design was employed. Data were successfully gathered from a sample of 9 learners and 1 teacher. The participants were purposely selected from the Vhembe District’s rural based secondary school. Three instruments were used to collect data: non-participant observation, text analysis, and the semi-structured interviews. Data were triangulated and analyzed using two data analysis techniques, namely: content analysis for data collected through text analysis and the thematic data analysis for the semi structured interview and observation data sets. This study revealed that the learners’ level of exposure to the social media language that they use for informal communication unconsciously makes them commit language errors that result in the deformation, omission, and substitution of the key words or phrases that help construct meaning in their Tshivenḓa Home Language academic creative essays. Secondly, the study established that learners perceive the use of social media language in academic writing as an effective tool, as it helps them to save time. Learners do not understand the formal academic writing setting. Thirdly, teachers need better and effective language error-correction strategies since their use of dictation is evidently ineffective to redress the social media language challenges that their learners’ experience.
Thesis (M. Ed. (Language Education)) -- University of Limpopo, 2025
Keywords: Social media; Creative essay writing; Tshivenḓa Home Language; Essay; Language and languages in social media; Social media in education; Venda language -- Study and teaching (Secondary)